ASSESSMENT OF NATURAL RESOURCES FOR MARINE TOURISM OF SMALL ISLANDS IN THE ARU ISLANDS, MALUKU - Widiyastuti, Dyah (ITB Journal Publisher, LPPM ITB, 2018)
Marine tourism as a tourism product is one important attraction of natural tourism Indonesia today. The potential and attractiveness of marine tourism is huge and scattered in various areas, including the Aru Islands. Consisting of small islands and considered as outer region, Aru Islands as one of the districts in the Maluku province has potential for marine tourism-based coastal and small islands supported cultural potential, so it is suitable to be developed as a maritime destination. Marine tourism should be managed with conservation and ecological approach to community-based, it is in accordance with the conditions in which the tourist sites in the coastal area adjacent to the local community.The aims of this study were to identify potential marine tourism Aru Islands; to identify issues, challenges and formulate strategies and recommendations for marine tourism development that capable of accommodating the interests of society also the conservation of coastal and small islands. Resources for development of nature-based marine tourism were identified and assessed in the Aru Islands. The study results showed that as an archipelago, the Aru Islands have some 42 potential and attractiveness of a total of 88 marine tourism potential and attractions. Aru Islands also has the potential of unique and distinctive cultural and culinary for supporting the development of marine tourism. The formulation of Tourism development strategy for coastal marine and small islands focus on six points which are: (i) creating zoning which divides the development of marine tourism; (ii) development of good management of maritime tourism destination; (iii) develop marine tourism products that contribute to the conservation for the natural and cultural environment; (iv) development of products marine tourism products which based on community and tourism business partnerships that strengthening awareness of travel for the community; (v) the development of marine tourism facility which has less impact on the environmental degradation of coastal/island and efficient use of natural resources; (vi) development through creative and innovative marine tourism packages.Marine tourism as a tourism product is one important attraction of natural tourism Indonesia today. The potential and attractiveness of marine tourism is huge and scattered in various areas, including the Aru Islands. Consisting of small islands and considered as outer region, Aru Islands as one of the districts in the Maluku province has potential for marine tourism-based coastal and small islands supported cultural potential, so it is suitable to be developed as a maritime destination. Marine tourism should be managed with conservation and ecological approach to community-based, it is in accordance with the conditions in which the tourist sites in the coastal area adjacent to the local community. The aims of this study were to identify potential marine tourism Aru Islands; to identify issues, challenges and formulate strategies and recommendations for marine tourism development that capable of accommodating the interests of society also the conservation of coastal and small islands. Resources for development of nature-based marine tourism were identified and assessed in the Aru Islands. The study results showed that as an archipelago, the Aru Islands have some 42 potential and attractiveness of a total of 88 marine tourism potential and attractions. Aru Islands also has the potential of unique and distinctive cultural and culinary for supporting the development of marine tourism. The formulation of Tourism development strategy for coastal marine and small islands focus on six points which are: (i) creating zoning which divides the development of marine tourism; (ii) development of good management of maritime tourism destination; (iii) develop marine tourism products that contribute to the conservation for the natural and cultural environment; (iv) development of products marine tourism products which based on community and tourism business partnerships that strengthening awareness of travel for the community; (v) the development of marine tourism facility which has less impact on the environmental degradation of coastal/island and efficient use of natural resources; (vi) development through creative and innovative marine tourism packages.